Origin and function of the major royal jelly proteins of the honeybee (Apis mellifera) as members of the yellow gene family. (16th July 2013) - Buttstedt, Anja; Moritz, Robin F. A.; Erler, Silvio
ABSTRACT In the honeybee, Apis mellifera, the queen larvae are fed with a diet exclusively composed of royal jelly (RJ), a secretion of the hypopharyngeal gland of young worker bees that nurse the brood. Up to 15% of RJ is composed of proteins, the nine most abundant of which have been termed major royal jelly proteins (MRJPs). Although it is widely accepted that RJ somehow determines the fate of a female larva and in spite of considerable research efforts, there are surprisingly few studies that address the biochemical characterisation and functions of these MRJPs. Here we review the research on MRJPs not only in honeybees but in hymenopteran insects in general and provide metadata analyses on genome organisation of mrjp genes, corroborating previous reports that MRJPs have important functions for insect development and not just a nutritional value for developing honeybee larvae.